An archaeological field survey of part of the Black Mountain in south-east Dyfed: a contribution to the interpretation of economy and settlement in the region from prehistory to the early modern period - Ward, Anthony H. (1993)
A survey of archaeological sites was carried out across 60 km2 of the Black Mountain in south-east Dyfed, an upland common. These are described and placed in a putative chronological sequence against a palaeo-environmental backcloth. Sepulchral cairns are the earliest sites recorded, probably belonging to the early second millennium bc. House circles and homesteads may date to later prehistory and the early proto-historic period, while numerous rectangular foundations are probably the remains of Medieval, possibly later Medieval, settlement. Boundaries partition part of the landscape and there are stone clearance heaps and strips.